The Small “e” eLIFE - eLearning, eInteraction, eFuture, eEducation - Marta-Christina SUCIU; Teodora ABRAMIUC (TODORAN); Gheorghe-Alexandru STATIVĂ (Communications of International Proceedings, 2021)
Opportunities to explore the status of the e-Environment occur daily, from the online work-from-home models to online conferences as the current one, we adapt to be in the eLIFE. The current paper announces the development of the future environment, looking at four main aspects as of where we stand today, analyzing various data sources, reports of most prominent platforms in the current economy and business environment, while also proposing potential models for the future jobs and lastly into the future lifes of the professionals. eLIFE is a model proposed to encompass four main elements that shape the current research. The paper goes into a deep dive of the eLearning trends, eInteractions from the online work environment, eFuture of the jobs and one last element, the data around eEducation. While putting these four elements together like a new puzzle image, a potential new model proposed to be the eLIFE, the life with a small “e”, as it stands out as a tool for the future.
Keywords: E-Learning; E-Interaction; E-Future; E-Education